Gonococcal endocarditis: a rare complication of a common disease. Issue 7 (25th June 2004) - Shetty, A; Ribeiro, D; Evans, A; Linnane, S
Abstract : This report describes a case of gonococcal endocarditis in a 28 year old male patient with no history of previous valvular heart disease. More cases of gonococcal endocarditis (a rare complication of gonorrhoea) may occur with the increase in the incidence of gonorrhoea and the increase in resistance to ciprofloxacin, which is currently used as the first line agent for the treatment of gonorrhoea in 75% of genitourinary medicine clinics.